OPTIMASI PARAMETER PEMISAHAN Zr DALAM PEB U3Si2/Al PRA IRADIASI MENGGUNAKAN METODE KROMATOGRAFI PENUKAR ANION - Yanlinastuti, Yanlinastuti; Noviarty, Noviarty; Haryati, Iis; Fatimah, Syamsul; Boybul, Boybul; Ginting, Aslina Br. (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Determination of optimum parameters in the process of zirconium separation from U3Si2/Al fresh fuel solution by anion exchanger chromatography and analysis with UV-Vis spectrophotometer has been carried out. Zirconium is one of isotopes that can be used in the determination of fuel burn-up. The purpose of this study is to obtain optimal parameters of zirconium separation in standard materials as well as U3Si2/Al fresh fuel solution by anion exchanger chromatography. Optimization of Zr separation parameters was carried out using Dowex 1x-8 resin with a variation in weight of 0.5; 1.0; 1.5; 2.0 and 2.5 g, acidity of H2SO4 at 1; 2; 3; 4; 5 and 6 M, standard feed concentrations of Zr at 50; 100; 150 and 200 ppm and flow rate of 3M H2SO4 elution at 0.1; 0.3; 0.5; 0.7 and 0.9 mL/minute. To the Zr effluent as the result of separation was added Arsenazo III 0.1% as complexing agent, and subsequent analysis with UV-Vis spectrophotometry was done at a wavelength of 665.3 nm. The measurement results show that the optimal parameters of Zr separation are the use of 1.5 g resin with resulting recovery of 70.79%, acidity of 3M H2SO4 with recovery of 83.94%, feed concentration of 150 ppm with recovery of 87.64% at a flow rate of 0.5 mL/minute. When those optimal parameters were used in Zr separation from U3Si2/Al fresh fuel solution, the recovery obtained was 96.23%. These optimized parameters can also be used to separate Zr from U3Si2/Al irradiated fuel solution.